Optimal determination of purchaser's order quantity and producer's process mean. - Chen, Chung-Ho (Journal of Applied Science and Engineering)
Determination of optimum mean of the process characteristic is an important theme in quality improvement. Meanwhile, economic selection of order quantity is a key factor in inventory management since an inappropriate order quantity may result in unreasonably high inventory or stockout cost. In the present paper, we modify Chen and Liu's model [8] to simultaneously determine the optimal purchaser's order quantity and producer's process mean by incorporating an asymmetric loss function. The solution procedure for this modified model is developed and numerical examples are given for illustration. Based on the sensitivity analyses, the common parameters having significant effects on the expected total profit of the system are the selling price per unit to the customer (R) and the mean demand of customer (ux). Therefore, accurate estimation of R and ux in order to obtain the optimal control on the order quantity and the maximum expected total profit of the system would be highly desired.